Morphological, Biochemical and Molecular Characterization of Ten Rhizobial Bacteria Isolates. - Al-Judy, Neamat; Majeed, Raffal (Iraqi Journal of Science, 2024)
This study was done in biotechnology laboratories in the national center of organicfarming /ministry of agriculture where ten of Rhizobial isolates and strain studied wereeither local isolate from chickpea root nodules or non- local (Syrian and Turkish)obtained from ICARDA.These isolates were identified and characterized on the basis ofcolonies morphology and biochemical tests including gram staining, catalase andoxidase tests. The Genetic diversity among the isolates was assessed by RAPD(RandumAmplified Polynorphic DNA)-PCR(Polynerase Chain Reaction) finger printing by usingfive primers. The RAPD result showed high ability to detect genetic polymorphism inRhizobia and have the ability to generated unique bands (marker) especially in Shiekhan3(10)bands Mosle(8)bands isolates that isolated from chickpea plants .